Placement of a 6 mm, fully covered metal stent for main pancreatic head duct stricture due to chronic pancreatitis: a pilot study (with video). (September 2016) - Ogura, Takeshi; Onda, Saori; Takagi, Wataru; Kitano, Masayuki; Sano, Tastsushi; Okuda, Atsushi; Miyano, Akira; Masuda, Daisuke; Takeuchi, Toshihisa; Fukunishi, Shinya; Higuchi, Kazuhide
Background: Temporary stent placement is widely performed for pancreatic duct stenosis due to chronic pancreatitis. A fully covered self-expandable metal stent (FCSEMS) has a larger diameter, and therefore longer stent patency, and the effect of expansion of the main pancreatic duct stricture may be obtained. However, if stent migration upstream occurs, stent removal is extremely difficult. In addition, because of the diameter gap between the FCSEMS and the main pancreatic duct, stent-induced ductal change may occur. To prevent these adverse events, the technical feasibility, safety and efficacy of the placement of a novel 6 mm diameter FCSEMS with a long suture, to facilitate its removal in cases of stent migration upstream, were evaluated in a pilot study. Methods: Between December 2014 and August 2015, symptomatic chronic pancreatitis patients with abdominal pain and a main pancreatic head duct stricture were enrolled. Stent placement for main pancreatic duct stricture was performed under endoscopic retrograde cholangiopancreatography (ERCP) guidance and stent removal was performed within 6 months. Results: A total of 13 patients were retrospectively enrolled in this study. Metal stent insertion was successfully performed in all patients and clinical success was high (12/13, 92%). As adverse events, stent migration upstream was seen in two patients. Another 11 patients successfully underwent stent removal without any adverse events. During follow up (median 258 days), 2 patients still underwent pancreatic duct stenting because of continuing main pancreatic duct stricture. Conclusion: In conclusion, this novel FCSEMS is acceptable for stent placement in cases of chronic pancreatitis with a main pancreatic duct stricture.